The inositol regulon controls viability in Candida glabrata - Bethea, Emily K. (Microbiology Society, 2010)
Inositol is essential in eukaryotes, and must be imported or synthesized. Inositol biosynthesis in Saccharomyces cerevisiae is controlled by three non-essential genes that make up the inositol regulon: ScINO2 and ScINO4, which together encode a heterodimeric transcriptional activator, and ScOPI1, which encodes a transcriptional repressor. ScOpi1p inhibits the ScIno2-ScIno4p activator in response to extracellular inositol levels. An important gene controlled by the inositol regulon is ScINO1, which encodes inositol-3-phosphate synthase, a key enzyme in inositol biosynthesis. In the pathogenic yeast Candida albicans, homologues of the S. cerevisiae inositol regulon genes are ‘transcriptionally rewired’. Instead of regulating the CaINO1 gene, CaINO2 and CaINO4 regulate ribosomal genes. Another Candida species that is a prevalent cause of infections is Candida glabrata; however, C. glabrata is phylogenetically more closely related to S. cerevisiae than C. albicans. Experiments were designed to determine if C. glabrata homologues of the inositol regulon genes function similarly to S. cerevisiae or are transcriptionally rewired. CgINO2, CgINO4 and CgOPI1 regulate CgINO1 in a manner similar to that observed in S. cerevisiae. However, unlike in S. cerevisiae, CgOPI1 is essential. Genetic data indicate that CgOPI1 is a repressor that affects viability by regulating activation of a target of the inositol regulon.